Design Thinking for Student Projects - Morgan, Tony (SAGE Publications, Ltd. (UK), 2022)
Employers look for more than just a good degree. Candidates are expected to be able to creatively solve problems, manage change, demonstrate commercial awareness, and collaborate and communicate at different levels. Increasingly, universities are helping their students gain these skills through team-based projects, utilising innovation to solve real-world problems. Created with direct input from students and packed with advice and guidance from leading industry experts, this textbook walks readers through the steps necessary to deliver a team-based project, facilitating the development of key employability skills along the way. Readers can also connect with each other and create their own projects and teams via the book’s LinkedIn group. Suitable for undergraduates and postgraduates across all disciplines undertaking team-based modules and courses, as well as those studying independently, Design Thinking for Student Projects is the essential guide to learning practical Design Thinking and employability skills. Tony Morgan is an Associate Professor in Innovation Management Practice at the University of Leeds. Lena J. Jaspersen is a University Academic Fellow in Innovation Management at the University of Leeds.